MANAGEMENT OF ORGANIZATIONAL CHANGE: CHALLENGES IN THE DIGITAL ERA - Mariana ȘENDREA; Viorica GRECEA (Economica)
Organizational change has become an im- perative in today’s business environment, marked by complex processes that impact the activities of all organizations, regardless of their field of activity, prompting them to adapt to new realities. This article addresses both theoretical and prac tical dimensions of effective change management, with particular emphasis on a specific type of change currently affecting all organizations: digital transformation. The study highlights the essence of organizational changes and examines the impact of management on stakeholders, with special attention to the issue of resistance to change and strategies to mitigate it. Digital transformation is presented as a prerequisite for organizational viability and long-term success in the digital era, supported by examples from selec ted companies. The article presents practical solu tions for efficient organizational change mana gement, emphasising the importance of a com prehensive and integrated approach to the factors influencing the change outcome.